APRENDIZAGEM HISTÓRICA NA PRÉ-ESCOLA: UM OLHAR PARA A ESTRUTURA CURRICULAR DA EDUCAÇÃO INFANTIL - Joana Ávila da Silva Souza (2024)
ABSTRACT The present work aims to analyze curricular documents that guide Early Childhood Education, namely, the DCNEIs (1999, 2010 and 2013), the BNCC (2018), the CRMS (2019), and the Curricular Guidelines of the REME of Três Lagoas (2019), as well as the organization of the Historical Learning process in preschoolers to verify whether there are elements that favor the construction of historical knowledge, through fields of experience, in order to contribute to the formation of the child as a subject and agent of transformation of its reality. The aim is to understand how the concept of Historical Learning is formed with a view to the formation of Historical Consciousness and its constitution in Early Childhood Education, investigating at a national, state and municipal level the legislation that structures and organizes it. The research undertakes a dialogue between Historical Education and Early Childhood Education, using as a theoretical contribution the contributions of the philosopher of History and historian Rüsen (1997, 2001, 2010, 2012 and 2014) who addresses Historical Learning from the perspective of the development of Historical Consciousness and the studies by historian and researcher Cooper (2002, 2006 and 2012) on Historical Learning for young children based on contact with historical sources. Both authors defend the development of historical reasoning from a young age, with a view to the formation of Historical Consciousness in children, so that, understanding themselves as social and historical subjects and imbued with the knowledge of the past, they can better understand the events of the present, applying this knowledge to their practical life. The methodological foundation used for this research is the hypothesis of historical knowledge based on Historical Epistemology, adopting bibliographic and documentary research as the operating mode of investigation, in a qualitative approach Ludke; André (2017). The analysis of the content of the documents is thematic, partly descriptive and partly reflective, following the principles suggested by Bardin (2016). The investigation comprised three phases: bibliographic research and literature review, which took place from research on platforms for articles, theses and dissertations on the topic, through Boolean search, using the AND and OR operators and keyword combinations: Early Childhood Education, Fields of Experience and Construction of Historical Consciousness. Subsequently, the guidelines and legal components that guide the constitution of the Early Childhood Educational field were selected and studied. In the last phase, we processed the information collected through the analysis of documents in the light of the Historical Learning theory, according to the theoretical assumptions mentioned before. We ascertained through this investigation that Historical Learning aimed at the formation of Historical Consciousness is discreetly presented in the legislation that regulates the Early Childhood Education curriculum. Keywords: Early Childhood Education - Fields of Experience - Construction of Historical Consciousness